A rare case of migration of ballistic projectile from left to right main bronchus (Medical Journal of Indonesia, 2022)
A foreign body in the bronchus due to a ballistic projectile is very uncommon. A 45-year-old man presented to the hospital after being accidentally shot. The initial radiographic assessment found a bullet in his left thoracic cavity. With the help of an X-ray, an urgent left posterolateral thoracotomy was conducted, but no foreign body was found. The foreign body had migrated to the contralateral chest cavity, as determined by the C-arm. On the following day, a thorax computed tomography scan was conducted, and it was discovered that the foreign body had already migrated to the right lower bronchus. A right thoracotomy was then performed to remove the foreign body. He was moved to the intensive care unit and discharged with a stable condition. In conclusion, migration of a foreign body in the bronchus is rare. A thorough strategy is required to prevent the object from migrating even further.